The East German wage structure in the transition to a market economy - Viktor Steiner; Lutz Bellmann (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1994)
An important question for the development of the East German labour market in the transition to a market economy is whether wage differentials by qualification, industry or region which were relatively small in the former GDR adjust to those in market economies which are more in line with differences in productivities and economic conditions. We estimate empirical earnings functions to quantify the contribution of various important factors shaping the earnings distribution in the East German transition process. Estimation is based on the first six waves of the Labour Market Monitor which is a representative panel data set of the East German workingage population covering the period 1990 to 1992. The specification of the estimated earnings functions is motivated by the various hypotheses of the development of the East German wage structure in the transformation process. Although we do find some similiarities with the existing wage structure in West Germany, the East German wage structure still differs in some important dimensions.
Keywords: 330